多通道混合数据采集系统设计与实现. - 严博 (Studia Poliana, 2020)
The static explosion test needs to collect multiple analog data output from multiple front-stage differential comb-shaped laser light curtain detectors at each measurement and control point. For the front-stage equipment, there are many channels, high time accuracy, and large data volume. A hybrid data acquisition system with autonomous capability was designed. This system can automatically remove invalid data and buffer the mixed signal composed of the bullet-shaped signal generated when the fragment passes through the curtain and the UTC time value corresponding to the bullet-shaped signal. And transmitted to the host computer. The system uses the FPGA + ARM architecture to complete the acquisition buffer task, automatically remove invalid data according to the configuration of the host computer and the threshold value, combined with GPS to tame the temperature-compensated crystal oscillator to synchronize the local clock with the UTC clock, and perform UTC on the collected bullet-shaped analog data The clock is marked to form a mixed data packet, which is transmitted to the upper computer through the USB2.0 bus high-speed mode. After actual testing, the design meets the requirements for the output signal of the front-stage detector in the static explosion test, the data volume is greatly reduced, the UTC time stamp accuracy meets the subsequent processing requirements, and the cost is low and the stability is high.